FINANCIAL INCLUSION IN STATE SECURITIES TRANSACTIONS AT BCA SYARIAH - Lemiyana; Agustina, Ria (Journal Of Islamic Ekonomic and Business, 2024)
BCA Syari'ah Bank makes efforts to support financial inclusion by collaborating with the Ministry of Finance in Sharia Securities transactions. The research method used by researchers is literature study using secondary data with BCA Syari'ah Bank as the research object. The results obtained are that there are various efforts made by Bank BCA Syari'ah to support financial inclusion and State Sharia Securities have an impact on the economy in Indonesia by increasing the amount of state budget revenue and providing opportunities for the investing community to support domestic development.